(Indentification of Phenol and Delphinidine in the Telangâs flower (Clitoria ternatea L.) and its effectivity to staphylococcus aureus as Eyes Bacterial Deseases) - Farida Hutajulu, Tiurlan; Sari, Rahma; -, Djumarman (Balai Besar Industri Agro, 2008)
Triglicoside, phenol and delphinidine are compounds, which is found in the telangs flower(Clitoria ternateaL.) Telangs flower usually used by the local people as traditional medicinal plant for eyes conjungtivitis desease caused by Staphylococcus aureus bacteria. The aim of the study is to know the effectivity of telangs flower on conjungtivitis. The preparate of the extracts was prepared by maseration of 1,3 and 5%of telangs flower using 100ml aquabidest for 24 hours. The extract was then freeze dried at-15C. The extract obtained was analised by Thin layer chromatography (TLC) using two types of eluentÂ (butanol: asetic acid: water = 4: 4: 2) and eluent (chioroform: methanol =9:1).The spots were obserbed visually under ultraviolet ray at 254 nm and the spots were scrape of, then disolve in 10ml of aquabidest. The extract then tested by Staphylococcus aureus bacteria using the paper diffusion method. The results show that the extract of telangs flower 1% contains 0.014% of delphinide, 0.020% phenol, and 3% extract were 0.016% of delphinidine, 0.022% phenol, and 5% extract were 0.017% of delphinedine, and 0.026% of phenol. The phenol compound 0.026%showed an inhibition areas of 0.87mm as antibacterial while delphinedine is just a blue pigment of telangs flower.